GDP-mannose pyrophosphorylase is an efficienttarget in Xanthomonas citri for citrus canker control - Alexandrino, André Vessoni; Barcelos, Mariana Pegrucci; Federico, Leonardo Bruno; da Silva, Tamiris Garcia; Cavalca, Lúcia Bonci [UNESP]; de Moraes, Carlos Henrique Alves; Ferreira, Henrique [UNESP]; Taft, Carlton Anthony; Behlau, Franklin; de Paula Silva, Carlos Henrique Tomich; Novo-Mansur, Maria Teresa Marques (American Society for Microbiology, 2024)
Xanthomonas citri subsp. citri (Xcc) is a bacterium that causes citrus canker, an economically important disease that results in premature fruit drop and reduced yield of fresh fruit. In this study, we demonstrated the involvement of XanB, an enzyme with phosphomannose isomerase (PMI) and guanosine diphosphate-mannose pyrophosphorylase (GMP) activities, in Xcc pathogenicity. Additionally, we found that XanB inhibitors protect the host against Xcc infection. Besides being deficientin motility, biofilmproduction, and ultraviolet resistance, the xanB deletion mutant was unable to cause disease, whereas xanB complementation restored wild-type phenotypes. XanB homology modeling allowed in silico virtual screening of inhibitors from databases, three of them being suitable in terms of absorption, distribution, metabolism, excretion, and toxicity (ADME/Tox) properties, which inhibited GMP (but not PMI) activity of the Xcc recombinant XanB protein in more than 50%. Inhibitors reduced citrus canker severity up to 95%, similarly to copper-based treatment. xanB is essential for Xcc pathogenicity, and XanB inhibitors can be used for the citrus canker control.
Keywords: citrus canker; citrus protection; GDP-mannose pyrophosphorylase; inhibitors; innovation; phosphomannose isomerase; Xanthomonas